2013
DOI: 10.1093/heapro/das074
|View full text |Cite
|
Sign up to set email alerts
|

Championing mental health at work: emerging practice from innovative projects in the UK

Abstract: SUMMARYThis paper examines the value of participatory approaches within interventions aimed at promoting mental health and wellbeing in the workplace. Specifically the paper explores data from the thematic evaluation of the Mental Health and Employment project strand within the Altogether Better programme being implemented in England in the Yorkshire and Humber region, which was funded through the BIG Lottery and aimed to empower people across the region to lead better lives. The evaluation combined a systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 9 publications
2
23
0
Order By: Relevance
“…However, research has revealed that organizational culture specific factors may be key determinants of the effectiveness of organization-wide interventions focusing on mental health and wellbeing. Hence addressing unique organizational needs through creation of a 'healthy organization culture' and adopting a participatory and non-stigmatizing approach are identified as effective systemic methods (8). It is thus essential to acknowledge the full picture of the workplace environment and impact of the employee experience by putting employees at the centre.…”
Section: Enoka P Wickramasinghementioning
confidence: 99%
See 3 more Smart Citations
“…However, research has revealed that organizational culture specific factors may be key determinants of the effectiveness of organization-wide interventions focusing on mental health and wellbeing. Hence addressing unique organizational needs through creation of a 'healthy organization culture' and adopting a participatory and non-stigmatizing approach are identified as effective systemic methods (8). It is thus essential to acknowledge the full picture of the workplace environment and impact of the employee experience by putting employees at the centre.…”
Section: Enoka P Wickramasinghementioning
confidence: 99%
“…Pioneering this task under the Helping Great Britain Work Well Strategy, the Health and Safety Executive of United Kingdom (UK) has introduced Wellbeing Champion Program (WCP) in workplaces as a novel approach to implement employee wellbeing programs in the UK (8)(9). The wellbeing or business champions are identified as drivers to forward organizational change with the aim of producing a culture that promotes wellbeing specific to the respective work setting.…”
Section: Enoka P Wickramasinghementioning
confidence: 99%
See 2 more Smart Citations
“…The key adaption was the transfer of intervention implementation and evaluation from the research team to a workplace champion. This "train the champion" approach recognises that workplace champions, as the role models and drivers, are critical for successful and sustainable workplace change [11][12][13]. Notably, the translation of the Stand Up Australia intervention into a scalable and sustainable workplace health and safety program involves multiple phases [14].…”
Section: Introductionmentioning
confidence: 99%